Pengaruh Metode Pembelajaran terhadap Hasil Belajar Ta’limul Qur’an Siswa di SMP Khadijah Surabaya - Ningsih, Dessi Fitria; Mufaizah, Mufaizah; Huda, Masrur (YASIN, 2025)
Student learning outcomes are influenced by various factors, one of which is the use of methods in teaching. Educational institutions need to more seriously consider teaching methods in the teaching and learning process. This study aims to determine the influence of teaching methods on the learning outcomes of Ta'limul Qur'an students at SMP Khadijah Surabaya. This research uses a quantitative method with a population of 439 students from grades IX, X, and XI. The sampling technique was carried out using the Quota Purposive Random Sampling method, where 20% of the population, or 88 students, were randomly selected. Data collection was conducted through questionnaires, observations, and documentation. The research location is at SMP Khadijah Surabaya, and data analysis was performed using SPSS version 25. Based on the results of a simple linear regression analysis, the significance level was 0.000 < 0.05, thus Ha was accepted. This indicates that there is a significant influence of teaching methods on the learning outcomes of students at SMP Khadijah Surabaya, with the contribution of teaching methods being 29.6% to the learning outcomes of Ta'limul Qur'an. These findings provide important insights into the influence of teaching methods on learning outcomes, particularly in the teaching of Ta'limul Qur'an.